Migrant Embodiments for the Right to Exist. The Case of the Immigrants Nationwide Coordinating Committee in Chile - Soto Márquez, Alexandra; Cubillos-Almendra, Javiera; Micheletti Dellamaria , Stefano (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
This article analyses the meanings developed by the members of the Immigrants Nationwide Coordinating Committee [Coordinadora Nacional de Inmigrantes] in opposition of those produced by the State’s necropolitical devices, which foster ideas such as “illegitimate bodies in the public space”, forcing the immigrant population to inhabit the zone of non-being. We use a qualitative approach based on interviews, corporeal cartographies and digital ethnography, jointly with a frame analysis. We were able to delve deeper into the corporal meanings produced within the Coordinating Committee — whose aim is to champion human rights of migrants in Chile —, particularly those linked to the struggle for the right to exists and to the demand that migrant bodies can be and remain in the territory.